Sociocultural Space in Lampung Architectural Buildings - Kustiani - Kustiani; Rendy Perdana Khidmat; Buyung Nasution (Jurnal Arsitektur, 2023)
The interpretation of traditional architecture within a sociocultural context refers to a notion of sustainability, where the value of sustainability is applied in the form of cultural changes between the traditional residential concept and the residential space system, which comprises physical, temporal, social, and conceptual space. The sociocultural context of traditional architectural space is one of the parameters that changes the morphology of space as a result of the long-term, repetitive behavior of occupants. Because of the correlation between space and human behavior occupying that space, spatial space exists. One of the values of traditional architecture is the application of social and symbolic information to the spatial relationships of these spaces. This research seeks to investigate the spatial connections of traditional house constructions by examining the proximity and complexity of spatial relationships between traditional homes and local social and cultural factors. This study employs a quantitative strategy based on the space syntax method. The obtained analysis results are in the form of Justified Graphs (j-graph) and Visibility Graph Analysis (VGA) with outputs of connectivity, integration, and intelligibility analysis. Based on the results of the syntactical analysis of the Relative asymmetry (RA) Value, the connectivity value, the integration value, and the intelligibility value, the Lamban Pesagi building has the highest syntactical value, with the spatial position that has the highest syntactical value being the pitak tengah room, which serves as a gathering place for the mother's family.